Differences in arachidonic acid levels and fatty acid desaturase (FADS) gene variants in African Americans and European Americans with diabetes or the metabolic syndrome - Sergeant, Susan; Hugenschmidt, Christina E.; Rudock, Megan E.; Ziegler, Julie T.; Ivester, Priscilla; Ainsworth, Hannah C.; Vaidya, Dhananjay; Douglas Case, L.; Langefeld, Carl D.; Freedman, Barry I.; Bowden, Donald W.; Mathias, Rasika A.; et al. (British journal of nutrition, 2012)
Over the past 50 years, increases in dietary n-6 PUFA, such as linoleic acid, have been hypothesised to cause or exacerbate chronic inflammatory diseases. The present study examines an individual's innate capacity to synthesise n-6 long-chain PUFA (LC-PUFA) with respect to the fatty acid desaturase (FADS) locus in Americans of African and European descent with diabetes or the metabolic syndrome. Compared with European Americans (EAm), African Americans (AfAm) exhibited markedly higher serum levels of arachidonic acid (AA) (EAm 7·9 (sd 2·1), AfAm 9·8 (sd 1·9) % of total fatty acids; P < 2·29 × 10− 9) and the AA:n-6-precursor fatty acid ratio, which estimates FADS1 activity (EAm 5·4 (sd 2·2), AfAm 6·9 (sd 2·2); P = 1·44 × 10− 5). In all, seven SNP mapping to the FADS locus revealed strong association with AA, EPA and dihomo-γ-linolenic acid (DGLA) in the EAm. Importantly, EAm homozygous for the minor allele (T) had significantly lower AA levels (TT 6·3 (sd 1·0); GG 8·5 (sd 2·1); P = 3·0 × 10− 5) and AA:DGLA ratios (TT 3·4 (sd 0·8), GG 6·5 (sd 2·3); P = 2·2 × 10− 7) but higher DGLA levels (TT 1·9 (sd 0·4), GG 1·4 (sd 0·4); P = 3·3 × 10− 7) compared with those homozygous for the major allele (GG). Allele frequency patterns suggest that the GG genotype at rs174537 (associated with higher circulating levels of AA) is much higher in AfAm (0·81) compared with EAm (0·46). Similarly, marked differences in rs174537 genotypic frequencies were observed in HapMap populations. These data suggest that there are probably important differences in the capacity of different populations to synthesise LC-PUFA. These differences may provide a genetic mechanism contributing to health disparities between populations of African and European descent.